Evaluation of the water quality in the effluent stations (Al-Wathba, Al-Sadr) within Al-Rusafa sector (Journal of the College of Basic Education, 2022)
This study was established to evaluate the quality of drinking water in two water purification plants in addition to four residential neighborhoods within the scope of these stations by measuring a number of physical and chemical properties per month and during the period from February until August 2017. The samples were collected from two outlets within the filter station (River outlet and collection tanks of sterile water after adding chlorine). The results showed that the values ​​of trihlomethane rise with rising temperature, pH, free chlorine and total organic carbon. The highest value of (78.957) μg / L was recorded in AL-Sadria area during the month of July. Also, four heavy metals (Pb, Zn, Al, Fe) were investigated and the results show that The concentrations of both aluminum and zinc were not exceed the international and Iraqi standard specifications, while The concentration of iron and lead exceeded these limits in some locations during the months of July and August. Also, Total organic carbon and Aerobic Plate Count, Coli and Streptococci were detected. In addition to measuring the pH, water temperature, electrical conductivity, total organic solids, turbidity, total hardness, the concentration of sulphate, chlorides and nitrates, and the results showed that the total organic carbon values were exceeded ​​ the Iraqi and international standards limits in some locations with the highest value of 1.89 mg /l During the month of July while the other factors did not exceed the standard limits.